2008
DOI: 10.1016/j.ijgo.2008.01.028
|View full text |Cite
|
Sign up to set email alerts
|

Effect of intestinal production of equol on menopausal symptoms in women treated with soy isoflavones

Abstract: Isoflavone supplementation improves menopausal symptoms only in women with the ability to produce equol.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
48
0
3

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(55 citation statements)
references
References 22 publications
1
48
0
3
Order By: Relevance
“…Legume, particularly soybean, is the most common source of isoflavones in human food. Moreover, it was well known that isoflavone-rich diets are associated with antitumor effect (Coward et al 1993), improving effect in cognitive function (Zhao and Brinton 2007), effect on menopausal symptoms (Jou et al 2008), and bone-sparing effects (Ishimi 2009). In soybeans, isoflavones are present as aglycones and glycosides: soy isoflavone glycosides are 3 glycosides (daidzin, genistin, glycitin), 3 malonylated glycosides (6"-O-Malonyl daidzin, 6"-0-Malonyl genistin, 6"-O-Malonyl glycitin), and 3 acetylated glycosides (6"-O-Acetyl daidzin, 6"-O-Acetyl genistin, 6"-0-Acetyl glycitin) while its aglycones are called daidzein, genistein, and glycitein, respectively (Kudou et al 1991;Zhu et al 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Legume, particularly soybean, is the most common source of isoflavones in human food. Moreover, it was well known that isoflavone-rich diets are associated with antitumor effect (Coward et al 1993), improving effect in cognitive function (Zhao and Brinton 2007), effect on menopausal symptoms (Jou et al 2008), and bone-sparing effects (Ishimi 2009). In soybeans, isoflavones are present as aglycones and glycosides: soy isoflavone glycosides are 3 glycosides (daidzin, genistin, glycitin), 3 malonylated glycosides (6"-O-Malonyl daidzin, 6"-0-Malonyl genistin, 6"-O-Malonyl glycitin), and 3 acetylated glycosides (6"-O-Acetyl daidzin, 6"-O-Acetyl genistin, 6"-0-Acetyl glycitin) while its aglycones are called daidzein, genistein, and glycitein, respectively (Kudou et al 1991;Zhu et al 2005).…”
Section: Introductionmentioning
confidence: 99%
“…(±)equol is the form that has been commercially available and mostly utilized in studies of its biological properties [9] although S-(-)equol is a natural diastereoisomer, exclusively produced by intestinal bacteria [7] and it preferentially activates estrogen receptor type β [10,11]. Equol may also have beneficial effects on bone health [12][13][14] and has been used for preventing and treating diseases such as cardiovascular disease [15], breast cancer [16] and climacteric symptoms [17]. Among these varied biological activities, there has been increasing recent attention on the antioxidative capacity of equol.…”
Section: Introductionmentioning
confidence: 99%
“…The results revealed that isoflavones had no beneficial effects in women who did not produce equol. Kupperman score for HF and excessive sweating showed a significantly greater reduction after isoflavone intake compared to placebo in women producing equol [73]. The results of this pilot study should encourage investigators to establish whether efficacy is influenced by equol production.…”
Section: Discussionmentioning
confidence: 79%
“…However, two studies are currently awaiting assessment: (i) Xue et al 2004 [34], which was not available and (ii) Jou et al 2008 [73], which was published after the performance of systematic literature search.…”
Section: Limitations Of This Reviewmentioning
confidence: 99%